Connection theory on differentiable fibre bundles: A concise introduction - Bozhidar Z. Iliev (International Journal of Mathematics and Mathematical Sciences)
The paper contains a partial review on the general connection theory on differentiable fibre bundles. Particular attention is paid on (linear) connections on vector bundles. The (local) representations of connections in frames adapted to holonomic and arbitrary frames are considered.